Research on Classification Technology for Customer Characteristic in Mobile Internet Scene - Qing Zhang (Dianxin kexue)
Based on the analysis of the characteristic of customer classification theory, the current mainstream webpage classification technology was summarized, and common mining algorithms and applicable scene of customer classification were deeply analyzed. Finally, the classification process of customer characteristic was discussed to provide practical reference for developing customer feature classification work under mobile internet.